Can Neuromodulation also Enhance Social Inequality? Some Possible Indirect Interventions of the State - Lavazza, Andrea (Frontiers in Human Neuroscience, 2017)
There is evidence that noninvasive brain stimulation (NIBS), and especially transcranial direct current stimulation (tDCS), can improve some cognitive functions, at least temporarily. However, as the improvement only applies to some “lucky” people, it may raise ethical, social, and legal issues related to fairness in selective contexts (exams, competitions, job interviews). In this regard, an important element tends to be overlooked: the variability in individual response to tDCS in particular. If intensive study or practice and massive doses of chemical enhancers can have slightly different effects over different people, transcranial direct current stimulation can sometimes be completely ineffective. The variability in individual response, if tDCS were widely used, could add to the already present natural inequalities between people, or even create new ones, leaving some in a disadvantaged condition. The discussion of the various ethical, social, and legal consequences of different individual responses to tDCS might also address a potential indirect intervention by the State. In fact, if NIBS were to be widespread in competitive contexts, those who do not benefit from tDCS would be disadvantaged compared to those able to enhance their skills thanks to neuromodulation technologies. The most disadvantaged people for their lower response to tDCS could then acquire the right to receive and use free and safe cognitive enhancing drugs or other forms of bettering cognitive skills and functions, so as to reduce the gap between them and those who respond well to tDCS, in the light of the principle of equal opportunity.